Lipid geochemistry in a sediment core from Conwy Estuary, North Wales - Masni Mohd Ali,; Stephen M. Mudge, (Universiti Kebangsaan Malaysia, 2005)
The sources and diagenesis of organic matter in sediment core from the Conwy Estuary, North Wales have been examined using lipid biomarker data (i.e. fatty alcohols and sterols). Twenty-five core sections were analysed from the surface to 50 cm depth. Sediments near the top of the core were enriched in marine organic matter with high concentration of short chain fatty alcohols and sterols, and decreased with depth. Terrestrial organic matter predominated the bottom sections of the core. These observations can be seen from the short/long ratio, Alcohol Source Index and Sterol Source Index, suggesting the degradation of the marine derived compounds. The sewage derived organic matter increased from bottom to top of the core showing the increasing input of sewage from the past until now. Multivariate statistical technique (PCA) was carried out to interpret the data. PCA confirmed above observations with PC1 and PC2 indicated biogeochemical sources.